The Effect of Spraying Proline Acid on Morphological Features of Egg plant Solanum melongena L. Exposed to Water Stress - AL-Bassam, Suha M. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was conducted in the glass house in a  nursery at the growth season 2013.The experiment was designed by  the Completely Randomized Blocks Design(CRBD).The seeds of two varieties of eggplant were studied.They were : 1.Lot (Number)Melaneana  an American species,2.Aydinsiyah a Turkish species.We used three periods of water stress(1,8 ,16)days  respectively, and three concentrations of proline acid (0,50,100) ppm using three frequents for each treatment.The experiment contained 54 experimental unit.The seeds were planted on the 30th/8/2013 in the glass house of the nursery, a month later, we put the plantelet in pots with good  fertilized soil in the glass house.Some growth features were studied (the height of the root and shoot system,dry weight for the leaf area and leaves number).The results showed a significant increase in some of the morphological features in the American spiecies (the dry weigh rate in the shoot and root system, the number of leaves rate and the leaf area) as they were compared to the Turkish variety and water stress for (8)days and spraying with the proline acid at concentration 50ppm for all trearments.